Domestic and international drivers of the demand for water resources in the context of water scarcity: A cross-country study - Rakesh Gupta; Kejia Yan; Tarlok Singh; Di Mo (Journal of Risk and Financial Management, 2020)
Global warming, while increasing human demand for water, is reducing water availability by reducing runoff flows and the effective amount of water between seasons, making water scarcity a growing problem globally. Water management plays an important role in mitigating global warming, improving the water cycle, reducing carbon emissions, and providing clean energy, and pricing water is considered a good approach to water management. Pricing water needs to take into account all sectors and aspects of society, such as domestic water, food and agriculture, energy, transport, industry, urban provision, human health, ecosystems, and the environment, and their interrelationships through water, within the context of the fundamental human rights to water and sanitation. This requires that every stakeholder should contribute to the development of water-related policies at every stage of the water interrelationship. This study investigated the relationship between water demand across different sectors of the economy using indicators for China, Australia, Japan, and the UK. Using panel analyses, this study finds that economic growth and population expansion increases the demand for water in all aspects. These findings have significant policy implications for water management. Because water prices can have an impact on global trade and, more importantly, are a major solution to global warming, water management policies should be considered at the global level, not only at the national level.
Keywords: 330; China; global warming; water management; water pricing; water scarcity